Pengaruh Pajak Daerah, Retribusi Daerah, Dan Pendapatan Asli Daerah Terhadap Belanja Modal Pada Kota Dan Kabupaten Di Provinsi Kalimantan Timur Tahun 2019-2023 - Aditya, Azizah Putri; Solikah, Mar’atus; Zaman, Badrus (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of Regional Taxes, Regional Levies, and Locally Generated Revenue (PAD) on Capital Expenditures in city/regency governments in East Kalimantan Province during the 2020–2023 period. The study is motivated by a mismatch between the increasing trend of PAD and the suboptimal allocation of Capital Expenditures, even though capital expenditure is a crucial component in infrastructure development and improving community welfare under regional autonomy. A quantitative associative approach was employed using multiple linear regression analysis. The data were obtained from the Regional Budget (APBD). The analysis included classical assumption tests (normality, multicollinearity, and heteroscedasticity), t-tests, F-tests, and the coefficient of determination (R²). The results show that partially, Regional Taxes and PAD significantly affect Capital Expenditures, while Regional Levies do not have a significant effect. However, simultaneously, all three variables significantly influence Capital Expenditures, with an R² value of 47.6%. These findings highlight the importance of optimizing PAD, particularly from the tax sector, to support productive and sustainable capital expenditures.The study concludes that strengthening regional fiscal independence through PAD optimization, along with enhancing transparency and public participation in financial management, is essential for supporting capital expenditure allocation aimed at development and public service improvement.